MIESZKALNICTWO W PLANOWANIU PRZESTRZENNYM LESZNA PO 1990 ROKU - Chudak, Mariusz (Space – Society – Economy, 2012)
The article presents the evolution of editing planning provisions with reference to the housing space and taking into consideration a chosen city. This evolution was taking place during the political transformation. Twelve studies passed after 1990 were analysed to help distinguish the most significant features of the process as far as single-family as well as multi-family housing is concerned. In addition, the location of a new-designed housing estate towards the centre and the surroundings is taken into account. Interpretation and then deduction are made with reference to the idea of shaping spatial order and the concept of sustainable development. It results from the necessity to preserve, in a relatively untouched condition, the most precious architectural and natural values of Leszno.